Perilaku Hijau untuk Efisiensi Energi sebagai Daya Dukung Kampus Berkelanjutan - Maslikhah Maslikhah; Roudlotul Jannah; Muna Erawati (Jurnal Penelitian Pendidikan IPA, 2022)
In order to make the environment safe and comfortable, humans need to have ethics. With good environmental ethics will make life more meaningful. Ethical towards the environment, among others, by protecting the environment from damage or loss. This study aims to analyze student behavior towards the use of electrical energy in providing sustainable campus carrying capacity. This field research is qualitative with a phenomenological approach to find out the daily, intersubjective world (world of life) of IAIN Salatiga students. This study reveals the meaning of concepts or phenomena of experience based on the awareness that occurs in IAIN Salatiga students in utilizing electrical energy on campus in lighting systems, air systems, and supporting equipment. Data collection techniques through observation, interviews, and documentation. The data that has been obtained is analyzed by reducing, presenting, and drawing conclusions or verification. Checking the validity of the data using triangulation techniques and sources. The results show that the behavior of IAIN Salatiga students is in the form of concern for the use of electrical energy, which includes lighting systems, air systems, and supporting equipment.